THE ROLE OF THE CONSTITUTIONAL COURT IN DECIDING DPT DISPUTES AND THE IMPLICATIONS OF THE CONSTITUTIONAL COURT DECISION NO. 102/PUU-VII/2009 - Rifat, Tb (JILPR Journal Indonesia Law and Policy Review, 2025)
The background of the problem in this research is related to the Constitutional Court Decision Number 102/PUU-VII/2009 which is a significant breakthrough in the Indonesian legal system, particularly in relation to guaranteeing citizens' constitutional rights in political participation. This decision regulates the use of population identity for prospective voters who are not registered in the Permanent Voter List (DPT), which was previously not permitted in the provisions of Article 28 and Article 111 of Law No. 42 of 2008. The purpose of this research is to analyze the implications of this decision in upholding justice and the constitutional rights of citizens. The benefit of this research is to provide a deeper understanding of the role of the Constitutional Court in safeguarding the political rights of Indonesian citizens. The method used is a case study with an analytical approach to the Constitutional Court Decision and relevant laws. The results of the study indicate that this decision provides space for prospective voters who are not registered in the DPT to still exercise their right to vote, thus restoring constitutional rights that were threatened with loss. This study highlights the importance of the Constitutional Court decision in safeguarding public political participation and its implications for the electoral system in Indonesia.